Matrix Methods in Economics - Almon, Clopper (Reading, Mass: Addison-Wesley Pub. Co., 1967)
This book is confined to a thorough explanation of matrix inversion, multiple regression, the analysis of variance and covariance, Lagrangian multipliers, linear and nonlinear programming, and the characteristic values of matrices.
Bibliography: p. 153-154.
ne 01/03/2018
Loan
Keywords: Matrices; Programming (Mathematics); Economics, Mathematical